2010
DOI: 10.1289/ehp.1001993
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Exposure during Pregnancy Disrupts Glucose Homeostasis in Mothers and Adult Male Offspring

Abstract: BackgroundBisphenol A (BPA) is a widespread endocrine-disrupting chemical used as the base compound in the manufacture of polycarbonate plastics. In humans, epidemiological evidence has associated BPA exposure in adults with higher risk of type 2 diabetes and heart disease.ObjectiveWe examined the action of environmentally relevant doses of BPA on glucose metabolism in mice during pregnancy and the impact of BPA exposure on these females later in life. We also investigated the consequences of in utero exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
276
4
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(320 citation statements)
references
References 40 publications
(56 reference statements)
24
276
4
4
Order By: Relevance
“…Perinatal exposure to BPA altered early adipogenesis and increased the body weight of offspring (Rubin & Soto 2009, Somm et al 2009. A brief exposure to BPA during pregnancy has also been found to initiate insulin resistance in adult offspring (Alonso-Magdalena et al 2010). Consistent with these findings, results from our previous study have confirmed that perinatal exposure to BPA resulted in a higher body weight and body fat percentage, a greater mass of white adipocytes, hyperlipidemia, hyperleptinemia, and insulin intolerance in adult rat offspring (Wei et al 2011).…”
Section: Introductionsupporting
confidence: 81%
“…Perinatal exposure to BPA altered early adipogenesis and increased the body weight of offspring (Rubin & Soto 2009, Somm et al 2009. A brief exposure to BPA during pregnancy has also been found to initiate insulin resistance in adult offspring (Alonso-Magdalena et al 2010). Consistent with these findings, results from our previous study have confirmed that perinatal exposure to BPA resulted in a higher body weight and body fat percentage, a greater mass of white adipocytes, hyperlipidemia, hyperleptinemia, and insulin intolerance in adult rat offspring (Wei et al 2011).…”
Section: Introductionsupporting
confidence: 81%
“…Several studies in rodent models have reported that perinatal exposure to BPA increases the body weight of offspring at 6 months of age (Alonso-Magdalena et al 2010) and in adulthood (Somm et al 2009) as well as in the neonatal period (Howdeshell et al 1999, Rubin et al 2001, Rubin & Soto 2009). However, Ryan et al (2010) reported a contrary result that oral exposure to BPA during the perinatal period did not induce glucose intolerance later in life in CD-1 mice.…”
mentioning
confidence: 99%
“…Progressive exposure to BPA can afect adiposity, glucose or insulin regulation, lipid proiles or other end-points relating to diabetes or metabolic syndrome [19][20][21][22][23][24][25][26][27].…”
Section: Bisphenol a And Human Healthmentioning
confidence: 99%